The dynamics of cooperation and conflict in the Black Sea area: From the region's history to current security challenges - Ioana Elena Secu (European Institute of Romania, 2023)
This paper aims to analyse the cooperation and security dynamics that characterise the Black Sea Region (BSR) since the Russian military aggression against Ukraine in February 2022, while also considering the major historical developments in the area. The study examines the interests and actions of various actors in the region, focusing on the European Union (EU), the North Atlantic Treaty Organisation (NATO), Turkey, the Russian Federation, Ukraine, and Romania. By using qualitative research and analysis of archival discoveries, governmental documents, official speeches, media news, and scientific papers, this working paper seeks to shed light on the complex political and security considerations that shape the future prospects of the Black Sea region.
Keywords: 330; Black Sea; European Union; NATO; Ukraine; security; war; geopolitics